Immunohistochemical expression of p16INK4A in the lesions of uterine cervix - Rawat, Niharika; Rajan, Shivapriya (Annals of Pathology and Laboratory Medicine, 2020)
Background: Cervical cancer is the major cause of cancer deaths among women. Globally, around 5,70,000 new cases of cervical cancer and 3,11,000 deaths occurred in the year 2018. In India, Cervical cancer is a leading cause of cancer related mortality among women and the number of deaths is 60,000 per year among 97,000 diagnosed patients, especially those from lower socioeconomic group. Human Papilloma Virus (HPV) plays a crucial role in causing cervical dysplasia. This is done by upregulating p16INK4A, a cyclin dependent kinase inhibitor through interaction with cellular regulatory proteins. Hence p16INK4A can be used as a biomarker, since it is directly related variable for the presence of HPV. This study was conducted to evaluate the expression of p16INK4A in benign, premalignant and malignant cervical lesions and to assess its utility in diagnosing and grading cervical lesions. Methods: A total of 80 cervical specimens categorized histopathologically into nonspecific cervicitis, low grade squamous intraepithelial neoplasia (LSIL), high grade squamous intraepithelial neoplasia (HSIL) and squamous cell carcinoma cervix were included in this prospective study of one-year duration. Immunohistochemical study of p16INK4A were interpreted qualitatively and semi-quantitatively by Allred scoring system (0 to 8 points) which measures the proportion of stained cells and intensity of staining of cells. The collected data were statistically analyzed by ANOVA and chi square test. Result: Qualitative method showed absence of p16INK4A expression in all nonspecific cervicitis. 16.7% (2/12) LSIL, 100% (12/12) HSIL and 100% (28/28) squamous cell carcinoma cases showed p16INK4A positivity. Allred scoring of p16INK4A showed 66% (8/12) HSIL and 85.7% (24/28) squamous cell carcinoma cases with score 3 positivity. Hence high-grade lesions showed higher expression of this marker. Conclusion: IHC expression of p16INK4A showed increasing degree of expression from benign to premalignant and malignant lesions suggesting its diagnostic and prognostic value in the cervical cancer management